Perceptions of Japan in Hungarian Turanism - Farkas, Mária Ildikó (Távol-keleti Tanulmányok, 2024)
The lively Hungarian interest in Asian cultures and Japan before 1945 had several motifs, one of them being the idea of Turanism, which was formed around the ethnic, linguistic, and cultural relation of the Turanian (Ural-Altaic) peoples (including Hungarians) in the late 19th century and affected public thinking until 1945 in Hungary. The secondary literature on Turanism seems to have increased in volume in the past decades with a notable emphasis on Hungarian Turanism, and some new research has examined the issue of Japanese Turanism, making a connection with Hungarian Turanism as well. As Hungarian Turanism is regarded as a significant promoter and mediator of Turanism to other regions, too, it is important to analyse the manifold nature of this phenomenon with comprehensive approaches. The paper focuses on the Hungarian background of the Japan-related Turanist ideas with a multifaceted examination and interpretation of Hungarian Turanism based on original research of the contemporary sources (including publications, archival documents of Turanist and Japan-related associations, newspaper articles, and reports on Japan-related events) and the available secondary literature. The paper also aims to examine what perceptions of Japan appeared in the ideas of Turanism, to present why and how Japan was attributed a special significance in Hungarian Turanism, and to analyse the origin, meaning, and the contemporary importance of this outstanding role. In the course of research, new aspects have arisen for examination: the perceptions impacted by the Japanese development of the late 19th and early 20th centuries and by the notion of the situation of Japan ‘between East and West’ as similar to that of Hungary; the debate on modernisation; the isolation of Hungary after the World War I; and the cultural achievements of Hungarian Turanism. Examining the complexity of the Hungarian historical, cultural, and political context of the early 20th century in connection to the perceptions of the East of that time in Hungary may provide a more complex interpretation and deeper understanding of the formation of Turanist ideas.